Serum fatty acids, biochemical indices and antioxidant status in goats fed canola oil and palm oil blend - Adeyemi, Kazeem Dauda; Sabow, Azad Behnan; Aghwan, Zeiad Amjad; Ebrahimi, Mahdi; Samsudin, Anjas Asmara @ Ab Hadi; Alimon, Abdul Razak; Sazili, Awis Qurni (BioMed Central, 2016)
Background: Dietary supplementation of unsaturated fats in ruminants, if not stabilized, can instigate oxidative stress which can have negative impact on production performance and enhance the susceptibility to various diseases. The current study examined the effect of dietary 80 % canola oil and 20 % palm oil blend (CPOB) on serum fatty acids, antioxidant profile and biochemical indices in goats. Thirty Boer bucks (4–5 months old; initial BW, 20.34 ± 0.77 kg) were randomly assigned to diets containing 0, 4 or 8 % CPOB and fed daily for a period of 90 days. Blood was sampled from the goats on 0, 30, 60 and 90 days of the trial and the serum was analyzed for fatty acids, cholesterol, glucose, total protein, antioxidants and lipid oxidation. Results: Neither diet nor sampling time influenced serum TBARS value, catalase, glutathione peroxidase and superoxide dismutase activities, LDL cholesterol, VLDL cholesterol, triglycerides, glucose and total protein. Goats fed 4 and 8 % CPOB had higher (P < 0.05) total cholesterol and HDL cholesterol than the control goats on day 30, 60 and 90. The proportion of C15:0 decreased with increasing level of CPOB on day 30 and 60. Serum C18:1n-9 increased with increasing level of CPOB in diet on day 60. The proportion of C18:3n-3 and C22:5n-3 increased (P < 0.05), while the proportion of C18:2n-6 decreased (P < 0.05) with increase in the level of CPOB on day 60 and 90. Dietary CPOB did not affect serum total carotenoid and δ-tocopherol but did increase (P < 0.05) α and γ-tocopherol. Conclusion: Dietary canola oil and palm oil blend could be supplemented in diets without instigating oxidative stress in goats.